Guerilla advertising weapon for promotional problems of selected smes in Mannar - Suganya, A.; Shivany, S. (University of Jaffna, 2017)
SMEs sector is fast growing, which needs specific market development for market survival and success. Today's contemporary marketing environment essentials new strategies for SMEs development. Lack of applied oriented research blocks the new strategies for this sector. Nowadays SME's are facing several marketing related issues. In all over the world many SME’s have applied Guerrilla marketing as the solution for their marketing problems. Guerilla advertising is one of the growing marketing techniques which are used by advertising industry that makes a use of unusual or unconventional means of promoting the product to the market. Modern and preferable methods of business promotional activities are always welcomed by the customer to improve the marketing problems in any sector. This research paper has triple objectives, as reviewing the Guerrilla Promotional strategies discovered in the literatures, identifying Guerilla advertising strategies from the practical applications in organizations, especially in small entities, and explore the Guerrilla advertising strategies for selected SMEs, which suffer from the promotional problems. Through the participatory research method, and the purposive sampling techniques, data were collected from four SMEs, rural development society members, Government officials and those who involve with SMEs in Mannar District. Discourse analysis was used to analyze the images which show Guerrilla advertising contents. There are six different weapons were identified from the literatures such as Ambient marketing, Guerrilla sensation, Ambush marketing, viral Marketing, Guerilla mobile and lower budget guerilla advertising on those methods. Even though there is no framework or guidelines for Guerilla Advertising methods recognized, present study recognized many Guerilla adverting practices form small, Medium and large companies. Finally, Researchers explored some Guerrilla advertising ideas to improve business promotions based on the concepts such as Ambient Marketing, Guerrilla sensation, Ambush Marketing and Viral Marketing.
Keywords: Ambient Marketing; Ambush Marketing; Guerilla advertising; Viral Marketing